Anaesthetic considerations for the surgical management of ocular hypotony in adults. Issue 2 (March 2023) - Chua, Alfred WY; Kumar, Chandra M; Harrisberg, Brian P; Eke, Tom
Ocular hypotony can occur from many causes, including eye trauma, ophthalmic surgery and ophthalmic regional anaesthesia–related complications. Some of these patients require surgical intervention(s) necessitating repeat anaesthesia. While surgical management of these patients is well described in the literature, the anaesthetic management is seldom discussed. The hypotonous eye may also have altered globe anatomy, meaning that the usual ocular proprioceptive feedbacks during regional ophthalmic block may be altered or lost, leading to higher risk of inadvertent globe injury. In an 'open globe' there is a risk of sight-threatening expulsive choroidal haemorrhage as a consequence of ophthalmic block or general anaesthesia. This narrative review describes the physiology of aqueous humour, the risk factors associated with ophthalmic regional anaesthesia–related ocular hypotony, the surgical management, and a special emphasis on anaesthetic management. Traumatic hypotony usually requires urgent surgical repair, whereas iatrogenic hypotony may be less urgent, with many cases scheduled as elective procedures. There is no universal best anaesthetic technique. Topical anaesthesia and regional ophthalmic block, with some technique modifications, are suitable in many mild-to-moderate cases, whilst general anaesthesia may be required for complex and longer procedures, and severely distorted globes.